EMPLOYABILITY SKILLS AND COMPETENCY REQUIRED BY INDUSTRIES: AN EMPIRICAL STUDY - Dr. Charul Jain; Ms. Sunakshi Tongia; Dr. Shweta Mishra (International Journal For Research In Educational Studies, 2024)
This study investigates the employability skills and competencies required by industries, and examines the relationship between competencies, employability, and trainability. A survey of 1,000 employees and 500 employers across various industries was conducted, and multiple regression analysis was used to examine the relationships between competencies, employability, and trainability. The results show that only 30% of employees possess the required employability skills, 25% have the necessary competencies, and 40% are trainable. The analysis also reveals that competencies such as problem-solving, adaptability, and communication are strong predictors of employability and trainability.